Cooperativismo: as vertentes do planejamento estratégico e planejamento estratégico participativo. - Sousa, Isabella Aguiar (Universidade Federal do Tocantins, 2020)
The present work aims to present through a bibliographical review how an appropriate participatory strategic planning can be done according to the concepts of cooperativism. The research was done through searches in books, articles and websites. In the course of the work, an introductory chapter is presented, in which the development of the research is outlined in general lines. It also presents cooperativism as a form of strategic management and the types of planning: strategic, tactical and operational. Each chapter is arranged as a development of the importance of planning, showing how it came about, its history and its definitions in each branch in which it is. This work seeks to show in a more detailed way each operation to be followed according to the type of planning and its particularities.